1983
DOI: 10.1002/aja.1001670203
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional reconstruction of a rat stage V Sertoli cell: II. Morphometry of Sertoli–Sertoli and Sertoli–germ‐cell relationships

Abstract: Sertoli--Sertoli and Sertoli--germ-cell configurational relationships were studied using morphometric techniques and direct measurements as obtained from micrographs used to reconstruct a model of a rat stage V Sertoli cell. Regional areas of the Sertoli cell surface, which faced germ cells, other Sertoli cells, or noncellular structures, were expressed as relative surface area percentages; and the absolute surface areas for these regional areas were calculated. The surface areas of the reconstructed cell, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 19 publications
8
91
0
2
Order By: Relevance
“…This possibility is not just novel, but perhaps essential physiologically, given the diverse cellular and molecular events that are occurring at the microenvironment of the BTB (Lie et al, 2009a). In addition, the number of differentiated Sertoli cells (Orth, 1982) that can support developing germ cells at a Sertoli/germ cell ratio of ϳ1:30 to 1:50 (Weber et al, 1983) in adult rat testes during the epithelial cycle is limited, with ϳ25 to 40 ϫ 10 6 Sertoli cells per testis. For instance, TNF␣ is known to perturb Sertoli cell TJpermeability barrier function by inhibiting the production of occludin, but not ZO-1, and by maintaining the proper level of occludin at the BTB, which is mediated by MMP-9 and collagens (Siu et al, 2003a).…”
Section: Cytokines and Steroids: Their Differential Effects On Blood-mentioning
confidence: 99%
“…This possibility is not just novel, but perhaps essential physiologically, given the diverse cellular and molecular events that are occurring at the microenvironment of the BTB (Lie et al, 2009a). In addition, the number of differentiated Sertoli cells (Orth, 1982) that can support developing germ cells at a Sertoli/germ cell ratio of ϳ1:30 to 1:50 (Weber et al, 1983) in adult rat testes during the epithelial cycle is limited, with ϳ25 to 40 ϫ 10 6 Sertoli cells per testis. For instance, TNF␣ is known to perturb Sertoli cell TJpermeability barrier function by inhibiting the production of occludin, but not ZO-1, and by maintaining the proper level of occludin at the BTB, which is mediated by MMP-9 and collagens (Siu et al, 2003a).…”
Section: Cytokines and Steroids: Their Differential Effects On Blood-mentioning
confidence: 99%
“…In fact, it has been reported that as much as ϳ40% of the Sertoli cell surface is in contact with elongated spermatids alone (Russell et al, 1986;de França et al, 1993), illustrating that the interaction between the Sertoli cell and this germ cell type is enormous. Indeed, a single Sertoli cell is known to support ϳ30-40 germ cells at different stages of development (Weber et al, 1983;Wong and Russell, 1983). Spermatogenesis is the process by which germ cells develop into mature spermatids under the influence of FSH, testosterone, LH, and estrogen (Steinberger, 1971;de Kretser and Kerr, 1988;Hess et al, 2001;Hess, 2003;Carreau et al, 2008).…”
Section: A Cellular Organization Of the Seminiferous Epithelium In Tmentioning
confidence: 99%
“…We noticed that donor cell colonization was less efficient in Cnot7 -/-than in Cnot7 and germ cells is intimate and multi-factorial. In fact, one Sertoli cell has contacts with multiple germ cells, as many as 50, which are different in their differentiation stage (Weber et al, 1983). Sertoli cells nurture and support those germ cells for their proliferation and differentiation by providing growth factors and nutrients.…”
Section: Introductionmentioning
confidence: 99%